Intrastriatal Chromospheres' Transplant Reduces Nociception in Hemiparkinsonian Rats. (1st September 2018) - Gómez-Paz, Alejandra; Drucker-Colín, René; Milán-Aldaco, Diana; Palomero-Rivero, Marcela; Ambriz-Tututi, Mónica
Highlights: 6-OHDA injection into rat's substantia nigra reduces mechanical, thermal and chemical thresholds. Chromospheres' transplant reverted 6-OHDA-induced allodynia and hyperalgesia. Antinociceptive effect induced by chromospheres was dopamine D2- and opioid-receptor dependent. Abstract: The present study evaluates the possible antinociceptive effect of chromosphere transplants in rats injected with 6-hydroxydopamine (6-OHDA), a model of Parkinson's disease. Male adult Wistar rats received 40 μg/0.5 μl of 6-OHDA or 0.5 μl of vehicle into the left substantia nigra (SNc). Rats were evaluated for mechanical allodynia, cold allodynia, thermal hyperalgesia and formalin. Rats with altered nociceptive threshold were transplanted with chromospheres. After transplant, rats were evaluated every week. Our results confirm that 6-OHDA injection into rat's SNc reduces mechanical, thermal, and chemical thresholds. Interestingly, chromospheres' transplant reverted 6-OHDA-induced allodynia and hyperalgesia. The antinociceptive effect induced by chromospheres was dopamine D2- and opioid-receptor dependent since sulpiride or naltrexone reverted its effect.